MYXEDEMA COMA - Munir, Atif (Journal of Ayub Medical College Abbottabad, 2017)
Myxedema may be the first presentation of patients with undiagnosed hypothyroidism. Definitive management is with thyroid hormone but supportive measures, identification and treatment of precipitating factors in an appropriately safe environment are vital. There is no consensus about preferred thyroid hormone regimen. Corticosteroid therapy is given until adrenal insufficiency has been excluded. We present here a case of seventy-four years old woman of myxodema coma Keywords: Myxedema; hypothyroidism; precipitating factors; adrenal insufficiency